Peran digital marketing terhadap minat beli pada Tiktok Shop dimediasi electronic word of mouth - Bagas, Stio; Nurfarida, Iva Nurdiana; Hidayat, Candra Wahyu (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
The research investigates the influence of digital marketing on purchase intention, and investigates the role of electronic word of mouth (e-WOM) as a mediator. The research was conducted on TikTok shop users in Malang City and took 120 people as research samples, data was collected using a questionnaire, and Path Analysis was carried out for hypothesis testing. The analysis results reveal that digital marketing influences consumer buying interest. Purchase intention is also influenced by e-WOM. However, digital marketing does not have a significant impact on e-WOM, thus e-WOM does not have a mediating role in the influence of digital marketing on the buying interest of Tiktok shop users.